Does anterior commissure involvement change the selection of treatment modality in early-stage glottic larynx cancer? - Dağdelen, Meltem; Yener, Haydar Murat; Hekim, Muhammed Veysel; Şahin, Merve; Tevetoğlu, Fırat; Kara Peker, Sinem; Aliyeva, Chinara; Yılmaz, Yetkin Zeki; Gözen, Emine Deniz; Karaman, Emin; Can, Günay; Uzel, Ömer Erol (Cerrahpaşa Medical Journal, 2023)
Objective: Glottic laryngeal cancers are detected at an early stage at the time of diagnosis. Radiotherapy (RT) or transoral laser microsurgery (TLM) as a local treatment is a choice for early glottic laryngeal cancer. This study aims to investigate the local control rate after RT or TLM for early-stage glottic laryngeal cancer (ESLC) with anterior commissure involvement. Methods: 119 patients with early-stage (Tis-T1-2) laryngeal cancer were treated in our institution with RT or TLM between 2009 -2021. The median follow-up time was 52 months. Seventy-three patients underwent TLM. Forty-six patients received RT, and there were 41 patients with anterior commissure involvement. Results: The 2 and 5 years overall survival (OS) rates were 92% and 73%, whereas local failure-free survival (LFFS) rates were 84% and 82% in all groups, respectively. The 2-year OS was 88% in the RT arm and 94% in the TLM arm, respectively. There was no statistically significant difference between the two treatment groups for OS (p: 0.062). According to anterior commissure involvement, twenty-nine underwent TLM, whereas 12 patients received radiotherapy. A total of 9 local failures occurred in the TLM group, there was no recurrence in the RT group (p:0.028). Conclusion: There was no statistically significant difference between the two treatment groups for LFFS, and OS. However, in the case of the anterior commissure involvement, 9 local failures occurred in the TLM group, and there was no recurrence in the RT group. RT might be recommended in ESLC, especially in patients with anterior commissure involvement.